2016
DOI: 10.1007/s13277-016-5191-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel VHLα isoform inhibits Warburg effect via modulation of PKM splicing

Abstract: Von Hippel-Lindau (VHL) is the most frequently mutated gene in clear cell renal carcinoma. Here, we identified a novel translational variant of VHL, termed VHLα, initiated from an alternative translational start site upstream and in frame with the ATG start codon. We showed that VHLα interacts with and regulates heterogeneous nuclear ribonucleoprotein A2B1 (hnRNPA2B1), which consequently modulates pyruvate kinase transcript splicing and reprograms cellular glucose metabolism. Our study demonstrated that a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…These results indicated the important roles of hnRNPA2B1 in mediating the pro-tumoral activities of c-myc, which was under stringent control by VHLα feedback loop. Notably, the greater inhibitory effects of VHLα than hnRNPA2B1specific shRNA suggested the other anti-tumor mechanisms of VHLα such as inhibition of hypoxia induced factor as previously described 18 . The pro-proliferative activities of hnRNPA2B1 was also uncovered by colony formation assay, wherein c-myc overexpression dramatically increased the colony number which was greatly reduced by either hnRNPA2B1 depletion or VHLα-proficiency (representative images and statistical data were provided in Fig.…”
Section: Vhlα Exerted Anti-tumoral Roles Through Negative Control Of supporting
confidence: 67%
See 4 more Smart Citations
“…These results indicated the important roles of hnRNPA2B1 in mediating the pro-tumoral activities of c-myc, which was under stringent control by VHLα feedback loop. Notably, the greater inhibitory effects of VHLα than hnRNPA2B1specific shRNA suggested the other anti-tumor mechanisms of VHLα such as inhibition of hypoxia induced factor as previously described 18 . The pro-proliferative activities of hnRNPA2B1 was also uncovered by colony formation assay, wherein c-myc overexpression dramatically increased the colony number which was greatly reduced by either hnRNPA2B1 depletion or VHLα-proficiency (representative images and statistical data were provided in Fig.…”
Section: Vhlα Exerted Anti-tumoral Roles Through Negative Control Of supporting
confidence: 67%
“…Our previous study demonstrated that hnRNPA2B1 was significantly decreased by VHLα other than other isoforms, which was blockaded by proteasome inhibitor, MG132, and suggested the involvement of ubiquitination/ proteasome system-mediated protein degradation 18 . We also noticed that MG132 treatment caused increase of VHLα in addition to accumulation of hnRNPA2B1, which implicated the possible feedback regulation on VHLα.…”
Section: Direct Association Between Hnrnpa2b1 and Octadic Pentamer Rementioning
confidence: 94%
See 3 more Smart Citations